(untitled) (Law and world, 2018)
Since August 2011, the Prosecutor’s Offi ce launched witnesses and victims service coordinator., With the aim of criminal proceedings and the interests of victims and witnesses involved in the protection, support for their re-victimization and secondary prevention and investigation and trial stage, their awareness . The “victim and witness coordinator of the criminal justice process” discusses the victim and witness coordinator, sheioda what they do, as long as the legislation would be the coordinator of the concept of refl ection, a brief overview of the victim and witness coordinator in the United States and discussed implementation of the legislation Changes ielebuli victim and witness coordinator to strengthen functions and duties.